The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jcb.30344
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of VEGF and its role in pathological angiogenesis

Abstract: Over the last seven decades, a significant scientific contribution took place in the delineation of the implications of vascular endothelial-derived growth factor (VEGF) in the processes of angiogenesis. Under pathological conditions, mainly in response to hypoxia or ischemia, elevated VEGF levels promote vascular damage and the growth of abnormal blood vessels. Indeed, the development of VEGF biology has revolutionized our understanding of its role in pathological conditions. Hence, targeting VEGF or VEGFmedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 204 publications
0
20
0
1
Order By: Relevance
“…VEGFR: GBM is a highly vascularized tumor and anti-angiogenic therapies have been widely investigated for its treatment [ 39 ]. VEGF is implicated in the process of angiogenesis [ 40 ]. It is activated in hypoxic conditions by translocation of hypoxia-inducible transcription factors (HIF1α and HIF1β) to the nucleus.…”
Section: Pathophysiology Of Gbm and Role Of Tksmentioning
confidence: 99%
“…VEGFR: GBM is a highly vascularized tumor and anti-angiogenic therapies have been widely investigated for its treatment [ 39 ]. VEGF is implicated in the process of angiogenesis [ 40 ]. It is activated in hypoxic conditions by translocation of hypoxia-inducible transcription factors (HIF1α and HIF1β) to the nucleus.…”
Section: Pathophysiology Of Gbm and Role Of Tksmentioning
confidence: 99%
“…We also applied VEGF from October 6, 2020, to February 26, 2021; in this interval, the patient exhibited improvements in verbal memory, executive function, and cognitive flexibility associated with the regeneration of MCA branches. Angiogenesis may be induced by VEGF in pathological conditions such as brain ischemia, as shown previously [12]. Progranulin may also play an important role in the recovery of memory and frontal lobe functions by enhancing the neurogenesis of the frontal and temporal lobes, as shown in a mouse model of ischemia [6,13].…”
Section: Es Journal Of Case Reportsmentioning
confidence: 68%
“…Angiogenesis and abnormal microvessels are important links in the pathogenesis of PSO, particularly vascular changes that precede epidermal hyperplasia in PSO . Angiogenesis is closely related to the VEGF signaling pathway, especially the key target VEGFA . It has been reported that VEGFA could promote the aggravation of PSO, and targeting VEGFA signaling in the epidermis could prevent the continued development of PSO …”
Section: Resultsmentioning
confidence: 99%